Progressive Multifocal Leukoencephalopathy following Treatment with Rituximab in an HIV-Negative Patient with Non-Hodgkin Lymphoma: A Case Report and Literature Review. Issue 6 (December 2014) - Felli, Valentina; Di Sibio, Alessandra; Anselmi, Monica; Gennarelli, Antonio; Sucapane, Patrizia; Splendiani, Alessandra; Catalucci, Alessia; Marini, Carmine; Gallucci, Massimo
Progressive multifocal leukoencephalopathy (PML) is a rare rapidly progressive demyelinating disease of the central nervous system caused by reactivation of latent John Cunningham (JC) polyomavirus (JCV) infection. We describe an unusual case of PML in a 54-year-old patient with follicular non-Hodgkin lymphoma who received rituximab plus cyclophosphamide, hydroxydaunorubicin, oncovicin and prednisolone (R-CHOP) therapy. She started to notice gradual progressive neurological symptoms about two months after completion of rituximab treatment and was therefore admitted to hospital. On admission, brain CT and MRI showed widespread lesions consistent with a demyelinating process involving the subcortical and deep white matter of the cerebral and cerebellar hemispheres. CT and MRI findings were suggestive of PML, and JC virus DNA was detected by polymerase chain reaction assay of the cerebrospinal fluid and serum. The patient was treated supportively but reported a progressive worsening of the clinical and radiological findings. Our report emphasizes the role of CT and MRI findings in the diagnosis of PML and suggests that PML should be considered in patients with progressive neurological disorders involving the entire nervous system and mainly the white matter, especially in the presence of previous immunomodulatory treatment or immunosuppression.